Design of a high resolution SLD-OCT and its application - Phua, Soo Fan. (2009)
OCT is an interferometric technique, relying on interference between a split and later recombined broadband optical field. The axial resolution of an OCT system is determined by the temporal coherence of the light source: light sources with shorter coherence length provide better resolution.